How Popular Musicians Learn: A Way Ahead for Music Education - Green, Lucy (Ashgate Popular and Folk Music Series, 2017)
Popular musicians acquire some or all of their skills and knowledge informally, outside school or university, and with little help from trained instrumental teachers. How do they go about this process? Despite the fact that popular music has recently entered formal music education, we have as yet a limited understanding of the learning practices adopted by its musicians. Nor do we know why so many popular musicians in the past turned away from music education, or how young popular musicians today are responding to it. Drawing on a series of interviews with musicians aged between fifteen and fifty, Lucy Green explores the nature of pop musicians' informal learning practices, attitudes and values, the extent to which these altered over the last forty years, and the experiences of the musicians in formal music education. Through a comparison of the characteristics of informal pop music learning with those of more formal music education, the book offers insights into how we might re-invigorate the musical involvement of the population. Could the creation of a teaching culture that recognizes and rewards aural imitation, improvisation and experimentation, as well as commitment and passion, encourage more people to make music? Since the hardback publication of this book in 2001, the author has explored many of its themes through practical work in school classrooms. Her follow-up book, Music, Informal Learning and the School: A New Classroom Pedagogy (2008) appears in the same Ashgate series. Lucy Green is Professor of Music Education at the Institute of Education, University of London. Her other books include Music, Informal Learning and the School: A New Classroom Pedagogy (2008); Music, Gender, Education (1997) and Music on Deaf Ears (1988). Contents: Foreword, Robert Fripp; What is it to be musically educated?: Research methods; Concluding thoughts; Skills, knowledge and self-conceptions of popular musicians: the beginnings and the ends: The ’beginnings’; Professional musicianship: the ’ends’; Some self-conceptions of popular musicians; Learning to play popular music: acquiring skills and knowledge: The overriding learning practice: listening and copying; Peer-directed learning and group learning; Acquiring technique; Practice; Acquiring knowledge of technicalities; Summary; Attitudes and values in learning to play popular music: Discipline and osmosis; Enjoyment; Valuing musicianship; Valuing oneself; Attitudes to ’other’ music; Summary; Popular musicians in traditional music education: Classical instrumental tuition; Traditional classroom music education; Summary; Popular musicians in the new music education: Popular music instrumental tuition; The new classroom music education; Popular music in further and higher education; The musician’s views of popular music in formal education; Summary; The formal and the informal: mutual reciprocity or a contradiction in terms?: The neglect of informal learning practices in formal music education; Informal learning practices, attitudes and values: their potential for the formal sphere; What can teachers do?; Appendix: summary profiles of the musicians; Bibliography; Index.